2014
DOI: 10.3329/jbau.v11i1.18206
|View full text |Cite
|
Sign up to set email alerts
|

Major nutrient contents and their uptake by brinjal as influenced by phosphorus and sulphur

Abstract: A pot experiment was conducted in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh to evaluate the influence of phosphorus (P) and sulphur (S) on major nutrient contents and their uptake by brinjal (cv. BARI brinjal-8) during the period from October, 2011 to May, 2012. The experiment was laid out in a completely randomized design with 12 treatments and 3 replications using four levels of P (0, 30, 60 and 90 kg P ha-1) and three levels of S (0, 15 and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…(2016) who found the maximum leaf area of A. vera with the application of 4 g S pot −1 compared to 2 g S pot −1 . This result can be further supported by the findings of previous studies where application of 30–45 kg S ha −1 showed significantly higher leaf area of different crops than the control treatment ( Khanom et al., 2008 ; Hasan et al., 2013 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…(2016) who found the maximum leaf area of A. vera with the application of 4 g S pot −1 compared to 2 g S pot −1 . This result can be further supported by the findings of previous studies where application of 30–45 kg S ha −1 showed significantly higher leaf area of different crops than the control treatment ( Khanom et al., 2008 ; Hasan et al., 2013 ).…”
Section: Resultssupporting
confidence: 84%
“…Application of fertilizer, field or pot conditions and the choise of crops are the vital factors influencing the S requirements (Maniruzzaman et al, 2016). Hasan et al (2013) also found maximum yield and growth of brinjal by applying 45 kg S ha À1 .…”
Section: Sulphur Requirement For Aloe Vera Lmentioning
confidence: 95%
“…The incorporation of organic manures might have resulted in the formation of such organic chelates of higher stability. These results are in confirmatory with those reported by Hasan et al (2013) [9] and Azarmi et al (2008) [3] .…”
Section: Effect Of Organic Nutrient Sources On Soil Micronutrientssupporting
confidence: 93%